Depletion of Tumor-Associated Macrophages Slows the Growth of Chemically Induced Mouse Lung Adenocarcinomas - Fritz, Jason M.; Tennis, Meredith A.; Orlicky, David J.; Yin, Hao; Ju, Cynthia; Redente, Elizabeth F.; Choo, Kevin S.; Staab, Taylor A.; Bouchard, Ronald J.; Merrick, Daniel T.; Malkinson, Alvin M.; Dwyer-Nield, Lori D. (Frontiers in Immunology, 2014)
Chronic inflammation is a risk factor for lung cancer, and low-dose aspirin intake reduces lung cancer risk. However, the roles that specific inflammatory cells and their products play in lung carcinogenesis have yet to be fully elucidated. In mice, alveolar macrophage numbers increase as lung tumors progress, and pulmonary macrophage programing changes within 2 weeks of carcinogen exposure. To examine how macrophages specifically affect lung tumor progression, they were depleted in mice bearing urethane-induced lung tumors using clodronate-encapsulated liposomes. Alveolar macrophage populations decreased to ≤50% of control levels after 4–6 weeks of liposomal clodronate treatment. Tumor burden decreased by 50% compared to vehicle treated mice, and tumor cell proliferation, as measured by Ki67 staining, was also attenuated. Pulmonary fluid levels of insulin-like growth factor-I, CXCL1, IL-6, and CCL2 diminished with clodronate liposome treatment. Tumor-associated macrophages expressed markers of both M1 and M2 programing in vehicle and clodronate liposome-treated mice. Mice lacking CCR2 (the receptor for macrophage chemotactic factor CCL2) had comparable numbers of alveolar macrophages and showed no difference in tumor growth rates when compared to similarly treated wild-type mice suggesting that while CCL2 may recruit macrophages to lung tumor microenvironments, redundant pathways can compensate when CCL2/CCR2 signaling is inactivated. Depletion of pulmonary macrophages rather than inhibition of their recruitment may be an advantageous strategy for attenuating lung cancer progression.